Study on Engagement and Separation Process of Positive Trapezoid Jaw Clutch - Sun Dongmei; Wang Yu; Guo Zhanzheng (Jixie chuandong)
The basic principle of jaw clutch is introduced. The stage division of engagement process is carried out and the stages of smooth joint of the allowed speed differences is determined through the detailed analysis of engagement and separation process of positive trapezoid jaw clutch. The keeping engagement and separation conditions is studied and the calculation formula is given. The overload protection is analyzed and the maximum manipulating oil pressure of overload protection is given.